Management of water and hydrocarbons assets: Are you using your instinct more often than your intellect? - Boehl, Carla (The Asset Management Council, 2014)
This paper examines the influences involved in asset management decision making and consider frameworks for decision making. It draws on the author’s academic and professional experience in the mining and utilities industries, specifically in management of water, wastewater and hydrocarbons assets.